Two-stage identification of interconnected steady-state systems with cascade structure: A parametric approach - Hasiewicz, Zygmunt (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with selecting, within a stochastic framework, an approximate system model from a parametric candidate model set for a composite steady-state system with cascade structure, assuming mean-squared model output error as a measure of the model accuracy. With applications in mind, particular emphasis is laid on computational simplicity of the model search routine and an easy-to-use but suboptimal two-stage approach is proposed for solving the corresponding identification task.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka